Effect of pH shifts on IgE-binding capacity and conformational structure of tropomyosin from short-neck clam (Ruditapes philippinarum). (1st December 2015) - Lin, Haixin; Li, Zhenxing; Lin, Hong; Song, Yongna; Lv, Liangtao; Hao, Zina
Highlights: IgE binding capacity of tropomyosin can be affected by pH shifting. pH shifting can induce conformational structure changes of tropomyosin significantly. pH shifting to acidic range can be used for allergenicity reduction of tropomyosin. Abstract: The aim of the present study was to assess pH-induced changes in conformational structures and potential allergenicity of tropomyosin from short-neck clams. As defined with circular dichroism (CD), an unfolded structure was found at pH values ranging from 2.0 to 5.0, followed by the loss of secondary structure at pH of 1.0. Correspondingly, surface hydrophobicity was reduced by 97.7% when pH was reduced from 7.0 to 1.0. Further indirect ELISA and dot-blot results of pH shifted tropomyosin showed that potential allergenicity correlated well with structural changes, as well as with SGF digestibility. Allergenicity decreased significantly with unfolding of the protein and was stable when surface hydrophobicity recovered back to neutral conditions. These results showed that conformational changes in tropomyosin induced by pH shifting significantly influenced the allergenicity of tropomyosin, and that the resulting changes occurred predominately in the acidic pH range.